Strategic Leadership and Resource Management for Pedagogical Innovation in Rural Schools: A Systematic Literature Review - Miftah Hur Rahman Zh; Zahid Zufar At Thaariq; Mona Novita; Athia Nur Kamilah; Taufik (Qoumun: Jurnal Pengabdian Masyarakat, 2026)
Purpose of the study: Rural schools in Indonesia and other developing countries face persistent learning quality gaps because of constraints in resources, infrastructure, and teacher training, while the demand for pedagogical innovation continues to rise. This study aims to synthesize recent empirical evidence on how principals' strategic leadership and resource management facilitate pedagogical innovation in rural schools. Methodology: A systematic literature review (SLR) following the PRISMA 2020 protocol was conducted by searching Scopus, Web of Science, ScienceDirect, ERIC, and the Indonesian Garuda portal for articles published between 2015 and 2025. After multi-stage screening and quality appraisal using the Critical Appraisal Skills Programme (CASP) instrument, 38 articles were selected as the final corpus. Thematic analysis identified five core dimensions: (a) contextualized transformational and distributed leadership, (b) adaptive partnership-based resource management, (c) locally responsive pedagogical innovation, (d) teacher professional development through learning communities, and (e) participatory community governance. Main Findings: The findings reveal that resource scarcity is not the sole determinant of educational quality; strategic leadership that integrates moral vision, social mobilization, and technological integration can convert constraints into opportunities for innovation. Novelty/Originality of this study: This study contributes to educational management theory by proposing an integrative Strategic Resource Innovation Leadership (SRIL) framework for rural contexts, offering a novel synthesis that connects leadership, resource adaptation, and pedagogical innovation for resource-constrained rural schools.